Enhancing critical learning through an adaptive web application: A case study of lower secondary school students studying artificial intelligence technology - Autthawuttikul, Siwanit; Laisema, Sitthichai; Rodkroh, Pornpimon (Humanities, Arts and Social Sciences Studies, 2024)
This research aims to develop and study the effects of an adaptive web application on critical learning of artificial intelligence technology in students under the Suphan Buri and Nakhon Pathom Secondary Educational Service Area Office. The sample was divided into two groups: 4,264 lower secondary school teachers that were surveyed to create a needs analysis on media use, teaching management and readiness to use technology and a second group of 709 lower secondary school students who volunteered to use the adaptive web application. The research instruments consisted of 1) an opinion and guidelines survey for developing the adaptive web application, 2) an adaptive web application to enhance learning of artificial intelligence, 3) a learning style assessment, 4) a critical learning test on artificial intelligence technology, and 5) a student opinion questionnaire. Data were analysed using content analysis, frequency, percentage, mean, standard deviation, need assessment, one-way ANOVA, and hypothesis tests by paired sample t-test. The results showed that 1) the conditions for media use, teaching management and readiness to use technology were at a high level; 2) there was no significant difference between pre-test and post-test scores at 0.05 significance; 3) there was no significant difference between pre-test and post-test scores among the student learning styles at 0.05 significance; 4) there was no significant difference in the frequency of media use classified by learning style at 0.05 significance; and 5) the students’ opinions toward learning activities via an adaptive web application was at the highest level (M = 4.59, SD = 0.49).